Raman scattering and alternative current conduction mechanism of the high‐temperature phase transition in [(C4H9)4N]3Bi2Cl9. (29th December 2016) - Trigui, W.; Oueslati, A.; Hlel, F.; Bulou, A.
Abstract : The tri‐tetrabutylammonium nonachlorobibismuthate(III) was found to crystallize in the monoclinic P21 /n space group. Two reversible order–disorder phase transitions are observed at 434/430 K and 477/473 K by differential scanning calorimetry technique. The evolution of Raman wavenumber versus temperature shows a remarkable shifting of the bands associated to alkyl chains, suggesting that the phase transition is governed by the reorientational motion of the organic part [(C4 H9 )4 N] + . The analysis of Nyquist plots has revealed the contribution of two electrical active regions corresponding to the bulk mechanism and the distribution of grain boundaries. The AC conductivity is analyzed by different processes: the non‐overlapping small polaron tunneling model proposed as a closely good model for region I and the correlated barrier hopping attributed to the conduction mechanism for region II. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The evolution of Raman wavenumber versus temperature shows a remarquable shifting of the bands associated to alkyl chains, suggesting that the phase transition is governed by the reorientational motion of the organic part [(C4 H9 )4 N] + .